The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1159/000200900
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin versus Secretin in the Treatment of Actively Bleeding Gastric Erosions

Abstract: In a double-blind, prospective, randomized trial, 63 patients with actively bleeding gastric erosions were treated with somatostatin (31 patients) or secretin (32 patients). Both drugs were administered by intravenous infusions for 48 or 72 h. The active bleeding and the effect of the therapy was endoscopically established. Somatostatin had a significantly (p < 0.05) better effect on the control of bleeding (29 vs. 23 patients), transfusion requirements (5.8 vs. 7.4 units, p < 0.01) and on the need of surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…1,2 Results of animal studies have suggested that secretin affects the central nervous system and may function as a neurotransmitter. 3,4 Interest in secretin for the treatment of symptoms of autism spectrum disorders (ASDs) stemmed from a nonblinded, uncontrolled case series of 3 children with ASDs who received synthetic intravenous secretin during a routine endoscopy evaluation for gastrointestinal problems.…”
mentioning
confidence: 99%
“…1,2 Results of animal studies have suggested that secretin affects the central nervous system and may function as a neurotransmitter. 3,4 Interest in secretin for the treatment of symptoms of autism spectrum disorders (ASDs) stemmed from a nonblinded, uncontrolled case series of 3 children with ASDs who received synthetic intravenous secretin during a routine endoscopy evaluation for gastrointestinal problems.…”
mentioning
confidence: 99%